Surveys in Combinatorics 2013 - Blackburn, Simon R.; Gerke, Stefanie; Wildon, Mark J. (Cambridge : Cambridge University Press, 2013)
This volume contains nine survey articles based on the invited lectures given at the 24th British Combinatorial Conference, held at Royal Holloway, University of London in July 2013. This biennial conference is a well-established international event, with speakers from around the world. The volume provides an up-to-date overview of current research in several areas of combinatorics, including graph theory, matroid theory and automatic counting, as well as connections to coding theory and Bent functions. Each article is clearly written and assumes little prior knowledge on the part of the reader. The authors are some of the world's foremost researchers in their fields, and here they summarise existing results and give a unique preview of cutting-edge developments. The book provides a valuable survey of the present state of knowledge in combinatorics, and will be useful to researchers and advanced graduate students, primarily in mathematics but also in computer science and statistics.
Preface; 1 Graph removal lemmas; 2 The geometry of covering codes: small complete caps and saturating sets in Galois spaces; 3 Bent functions and their connections to combinatorics; 4 The complexity of change; 5 How symmetric can maps on surfaces be?; 6 Some open problems on permutation patterns; 7 The world of hereditary graph classes viewed through Truemper configurations; 8 Structure in minor-closed classes of matroids; 9 Automatic counting of tilings of skinny plane regions.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Combinatorial analysis; Graph theory